Chinese reluctance to report crime: Political efficacy, group care and hukou. (November 2022) - Wu, Yuning; Su, Ivan Y; Hu, Rong
Rising crime rates and strained police–community relations in China are calling for more research on people's crime-reporting desires and associated predictors. Drawing upon survey data collected from a sample of 757 local and nonlocal residents in a large city in Southern China, this study takes the initiative to assess Chinese people's reluctance to report crime to the police. Results show that a lower level of political efficacy, external efficacy specifically, is associated with a higher level of reluctance to report crime. The effects of group care are mixed, with the inner-circle care exerting a negative and the outer-circle care a positive association with crime-reporting desires. Furthermore, net of all controls, local hukou residents express lower levels of willingness than their nonlocal counterparts to report crime. Finally, the perception of police misconduct is the most significant and strongest predictor of Chinese people's reluctance to report crime. These findings suggest the importance of including a combination of both policing and non-policing factors when studying crime-reporting inclination, opening up an interdisciplinary perspective for studying the issue.